2004
DOI: 10.1152/ajpregu.00550.2003
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of EDHF-mediated responses in subcutaneous small arteries from healthy pregnant women

Abstract: Luksha, Leonid, Henry Nisell, and Karolina Kublickiene. The mechanism of EDHF-mediated responses in subcutaneous small arteries from healthy pregnant women. Am J Physiol Regul Integr Comp Physiol 286: R1102-R1109, 2004. First published January 29, 2004 10.1152/ajpregu.00550.2003.-We studied the importance of endothelium-derived hyperpolarizing factor (EDHF) vs. nitric oxide (NO) and prostacyclin (PGI2) in bradykinin (BK)-induced relaxation in isolated small subcutaneous arteries from normal pregnant women. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 40 publications
4
40
1
Order By: Relevance
“…These differences most likely result from an increasing contribution of EDHF in the control of vascular tone in the uterine and mesenteric circulation with decreasing vessel size. Our data are in agreement with ample evidence that EDHF is an important mediator of endothelial influences in microcirculation of animals and humans (6,7,9,11,13,25,28,30,33,36,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 92%
“…These differences most likely result from an increasing contribution of EDHF in the control of vascular tone in the uterine and mesenteric circulation with decreasing vessel size. Our data are in agreement with ample evidence that EDHF is an important mediator of endothelial influences in microcirculation of animals and humans (6,7,9,11,13,25,28,30,33,36,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it has been proposed that a decrease in the vascular expression of Cx43 alone or concomitantly with Cx40 could afford the reduction in EDHF-mediated responses in rat mesenteric arteries of ovariectomized rats , Xu et al 2002, Nawate et al 2005; this was substantiated by the observation that when animals were treated with 17b-estradiol, all responses were normalized (Chataigneau & Schini-Kerth 2005, Nawate et al 2005. In addition, it has been suggested that the increased EDHFmediated relaxation, associated with pregnancy in rats and humans (Pascoal & Umans 1996, Gerber et al 1998, Kenny et al 2002, is in part due to enhanced gap junctional communication at least in response to bradykinin in subcutaneous small arteries of pregnant women (Luksha et al 2004, Lang et al 2007). However, in rat middle cerebral arteries myoendothelial gap junction frequency does not correlate with the reduced EDHF responses observed in females compared with males (Sokoya et al 2007).…”
Section: Edhfmentioning
confidence: 93%
“…MEGJs and the gap junction protein, Cx43 (connexin 43), are the primary mechanisms underlying EDH in small resistance arteries isolated from subcutaneous fat biopsies from normal pregnant women. 37,38 The function of MEGJ was deficient in arteries from women with preeclampsia, contributing to reduced EDH involvement in dilatory responses to bradykinin. 39 Total relaxation to bradykinin, however, did not differ between normal pregnant and preeclamptic women.…”
Section: Endothelium-derived Hyperpolarizationmentioning
confidence: 99%